ANALISIS SOAL MATERI SISTEM GERAK MANUSIA BERDASARKAN KETERAMPILAN BERPIKIR TINGKAT TINGGI DI SMPN 1 BENGKALIS - Esy Meila Kurnia; Yustina Yustina; Arnentis Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to identify daily test items for the motion system material in humans based on higher-order thinking skills at SMPN 1 Bengkalis in the 2021/2022 academic year. This type of research is descriptive research. The research approach used is a qualitative approach. This research was conducted at SMPN 1 Bengkalis in January-June 2022. The type of data used is documents. The source of the data used is secondary data in the form of odd semester daily test questions on the human movement system in the form of multiple choice in the science subjects of SMPN 1 Bengkalis for the 2021/2022 academic year. The method of data collection is done by documentation study. The data analysis technique uses the Miles and Huberman model data triangulation which consists of data reduction, data presentation, conclusion drawing and verification. The results showed that the daily test questions on the human movement system material in the science subjects of class VIII SMPN 1 Bengkalis in the 2021/2022 academic year were mostly dominated by lower order thinking skills (LOTS) questions with a percentage of 80% and only about 20% or a small part of the questions. which is of the HOTS type and that is only at the C4 cognitive level (analyzing). Questions with cognitive level C1 (remembering) as many as 6 questions or 60%, C2 (understanding) as many as 2 questions or 20%, C3 (applying) not found in questions or 0%, C4 (analyzing) as many as 2 questions or 20%, C5 (evaluating) and C6 (creating) were not found in the questions or 0%.Key Words:Analysis, HOTS, LOTS, question